2021
DOI: 10.5194/wcd-2021-69
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Past Evolution and Recent Changes in Western Europe Large-scale Circulation

Abstract: Abstract. Detecting trends in regional large-scale circulation (LSC) is an important challenge as LSC is a key driver of local weather conditions. In this work, we investigate the past evolution of Western Europe LSC based on the 500 hPa geopotential height fields from 20CRv2c (1851–2010), ERA20C (1900–2010) and ERA5 (1950–2010) reanalyses. We focus on the evolution of large-scale circulation characteristics using three atmospheric descriptors that are based on analogy – characterizing the geopotential shape s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…We interpret this as a hint that small-scale organization may be necessary to large-scale transitions. Other local indicators also based on analogues such as the ones used by [24] and [25] shall also be considered in an attempt to predict transitions.…”
Section: Discussionmentioning
confidence: 99%
“…We interpret this as a hint that small-scale organization may be necessary to large-scale transitions. Other local indicators also based on analogues such as the ones used by [24] and [25] shall also be considered in an attempt to predict transitions.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the change in the rate of decrease of AOT, the total warming in Central and Eastern Europe has however increased at more or less the same rate after 1980, although somewhat faster for clear-sky condition compared to the all-sky situation. Beside enhanced greenhouse effect and reduced impacts from the aerosols, previous studies suggest changes in atmospheric circulation (Blanc et al, 2022;Sfică et al, 2020), which may have contributed to the rapid warming. The present finding of a substantial warming in Europe due to decreases in aerosols in addition to greenhouse warming is important and relevant when considering other regions on Earth in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Blanc et al. (2022) investigated possible changes in large‐scale circulation over the period 1950–2019 for Western Europe using European Centre for Medium‐range Weather Forecasts (ECMWF, Hersbach et al., 2019) ERA5 reanalysis. They found that anticyclonic conditions tend to become more stationary in summer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results relied on five data sets: four reanalysis sets and the fifth based on satellite retrievals from the Advanced Very High-Resolution Radiometers. Blanc et al (2022) (Dong et al, 2017). A set of experiments using the atmospheric component of the HadGEM3 global climate model were analyzed to understand the causes of the warming.…”
Section: Introductionmentioning
confidence: 99%